Using a compact combined constructed wetland system to treat agricultural wastewater with high nitrogen - Suwasa Kantawanichkul (2018)
The objectives of this study were to find appropriate conditions for nitrogen removal by a compact combined constructed wetland system and to evaluate the removal rate constant in a tropical climate. This study will present suitable operating conditions for a combined system to treat pig farm wastewater containing high ammonia-nitrogen. Four laboratory-scale combined constructed wetland units (0.5 × 1.0 × 1.0 m3): vertical flow vegetated bed over horizontal flow sand bed, were operated under an average temperature of 24 °C. Pig farm wastewater with COD and NH4+-N concentration of 1034 and 448 mg/L in average was fed to the system at different HLR from 2 to 8 cm/day. The porformance of the system when operated with a vertical flow bed followed by a horizontal flow bed or vice versa did not show a significant difference but under high HLR, nitrogen removal efficiencies were clearly reduced. Nitrobacter and Nitrosomonas were found in a large number in vertical flow beds and the same for denitrifier bacteria in a horizontal flow beds. Removal rate constants for nitrification (kNH4-N) were 0.0413 m/d for H-Vmode and 0.0339 m/d for V-H mode. Removal rate constants for denitrification (kNOx-N) were 0.0979 m/d for H-Vmode and 0.0399 m/d for V-H mode, respectively. © IWA Publishing 2005.